2015
DOI: 10.18646/2056.22.15-005
|View full text |Cite
|
Sign up to set email alerts
|

Do Feedback Environment and Coaching Communication Determine Self-Efficacy of Teaching? A Case of Malaysian Polytechnic Lecturers

Abstract: Abstract:This quantitative descriptive study aimed to identify the influence of coaching communication on the relationship between feedback environment and self-efficacy of teaching. In particular, the objective of this study was to identify whether the coaching communication would be able to become a mediator in the relationship between feedback environment and self-efficacy of teaching. A total of 411 lecturers randomly selected from the five three polytechnics which successfully obtained an overall excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Cavanaugh (2016) concluded that when SFE is favorable, accurate, encouraging and from a credible source, the employee propensity to learn and seek information for self-initiated learning increases. Literature shows that SFE has a direct association with personal factors such as self-efficacy, career insight and motivation to learn (Cavanaugh, 2016;Guzman, 2007;Leh et al, 2014;Ling and Abdullah, 2015) and influences both work engagement and informal learning (Cavanaugh, 2016;. Feedback environment is also verified as a moderator which strengthens the relationship of personal factors and dependent variables such as work engagement and available meaningfulness safety (e.g.…”
Section: Supervisor Feedback Environmentmentioning
confidence: 99%
“…Cavanaugh (2016) concluded that when SFE is favorable, accurate, encouraging and from a credible source, the employee propensity to learn and seek information for self-initiated learning increases. Literature shows that SFE has a direct association with personal factors such as self-efficacy, career insight and motivation to learn (Cavanaugh, 2016;Guzman, 2007;Leh et al, 2014;Ling and Abdullah, 2015) and influences both work engagement and informal learning (Cavanaugh, 2016;. Feedback environment is also verified as a moderator which strengthens the relationship of personal factors and dependent variables such as work engagement and available meaningfulness safety (e.g.…”
Section: Supervisor Feedback Environmentmentioning
confidence: 99%